Membandingkan Komitmen Pebisnis Katolik Jakarta terhadap Persoalan Kemiskinan dan Lingkungan Hidup dengan Peserta Ekonomi Fransiskus - Sule, Fransiskus; Daniel, Yusuf (Penamas, 2024)
This paper study the business practices of Catholic entrepreneurs. Employing qualitative research and conducting in-depth interviews with purposefully selected informants from the community of  Profesional dan Usahawan Katolik Keuskupan Agung Jakarta (Catholic Professionals and Entrepreneurs of the Archdiocese of Jakarta, PUKAT KAJ), the findings reveal a consistent alignment of their business strategies with Catholic faith principles. A comparative analysis of The Economy of Francesco's Final Statement and Common Commitment 2020 finds that Catholic businesspeople prioritize individual changes due to human dignity and equity, while participants stress the importance of structural changes for global justice. The authors propose the integration of The Economy of Francesco's principles, either partially or entirely, into PUKAT KAJ's vision and mission. This strategic alignment is recommended to enhance the societal impact of members' businesses and further promote the values upheld by The Economy of Francesco.